(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
As to impact of European level planning activities and initiatives on planning practice in the Member States of the European Union, an important issue is practical application of theoretical aspects of planning that includes results of discussions on basic conditions for elaboration of a high quality and effective integrated planning documents and concepts in accordance with theoretical conclusions. The significance of cities with regard to regional development is testified by political and strategic documents-the strategy "Europe 2020" (EC, 2010) and others. Attractiveness is now linked to economic growth to provide a broader framework for the analysis of the process during which cities will reach higher standards of their inhabitants' life quality, as well as the most favorable environment for attraction of investments and visitors. Therefore it is important to understand what creates the attractiveness of cities for residents, investors and visitors and the way it could become an element of policy and planning process to contribute to balanced regional development. The aim of the research is to explore the importance of elaboration of integrated development concepts to increase the city attractiveness and the way it could become an element of policy and planning process to contribute to balanced regional development. Three tasks have been set within the framework of the research: -to investigate the theoretical aspects of planning methodology and city attractiveness; -to identify the most important factors of city attractiveness for Rezekne city; -to set up the integrated regional development concepts' priorities of the Rezekne city to enhance its attractiveness.